Transformasi Pancasila Di Era Digital: Peluang Dan Tantangan - Ardiana Bulan Ramadhani; Fibri Nur Halizah; Hellya Untari; Maurilla Shafaa Anggraini; Meilina Ayu Kristina; Ari Metalin Ika Puspita (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
The development of digital technology and digital transformation has had a significant impact on Indonesian society. This article discusses the challenges and opportunities related to the transformation of Pancasila in the digital era. Through an analysis of democracy, Pancasila values, technological developments, and the challenges faced by Indonesian society, this article aims to understand how the noble values ​​of Pancasila can be applied in everyday life to maintain Indonesia's national identity. With a focus on building national character, protecting personal data, and implementing Pancasila values ​​in the face of globalization, this article highlights the importance of strengthening awareness of nationalism and national integrity in the digital era.